2021
DOI: 10.1021/acs.jctc.1c00372
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Profiling of Binding and Allosteric Propensities of the SARS-CoV-2 Spike Protein with Different Classes of Antibodies: Mutational and Perturbation-Based Scanning Reveals the Allosteric Duality of Functionally Adaptable Hotspots

Abstract: The functional adaptability and conformational plasticity of SARS-CoV-2 spike proteins allow for the efficient modulation of complex phenotypic responses to the host receptor and antibodies. In this study, we combined atomistic simulations with mutational and perturbation-based scanning approaches to examine binding mechanisms of the SARS-CoV-2 spike proteins with three different classes of antibodies. The ensemble-based profiling of binding and allosteric propensities of the SARS-CoV-2 spike protein residues … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 113 publications
(228 reference statements)
2
54
0
Order By: Relevance
“…The latest extensive molecular dynamics (MD) simulations and free-energy landscape mapping studies of the SARS-CoV-2 S proteins and mutants detailed conformational changes and diversity of ensembles, further supporting the notion of enhanced functional and structural plasticity of S proteins [57][58][59][60][61][62][63]. Our recent studies offered evidence that the SARS-CoV-2 spike protein can function as an allosterically regulated machine that exploits plasticity of allosteric hotspots to fine-tune response to antibody binding [64][65][66][67][68][69]. These studies showed that examining allosteric behavior of the SARS-CoV-2 S proteins may be useful to uncover functional mechanisms and rationalize the growing body of diverse experimental data.…”
Section: Introductionmentioning
confidence: 66%
“…The latest extensive molecular dynamics (MD) simulations and free-energy landscape mapping studies of the SARS-CoV-2 S proteins and mutants detailed conformational changes and diversity of ensembles, further supporting the notion of enhanced functional and structural plasticity of S proteins [57][58][59][60][61][62][63]. Our recent studies offered evidence that the SARS-CoV-2 spike protein can function as an allosterically regulated machine that exploits plasticity of allosteric hotspots to fine-tune response to antibody binding [64][65][66][67][68][69]. These studies showed that examining allosteric behavior of the SARS-CoV-2 S proteins may be useful to uncover functional mechanisms and rationalize the growing body of diverse experimental data.…”
Section: Introductionmentioning
confidence: 66%
“…In a recent study of dynamic profiling of binding and allosteric propensities of the SARS-CoV-2 spike protein with different classes of antibodies, it was seen that RBD mutation sites K417, E484, and N501 correspond to a group of versatile allosteric centers in which small perturbations can modulate collective motions, alter the global allosteric response, and elicit binding resistance. 49 …”
Section: Results and Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted July 8, 2021. ; https://doi.org/10.1101/2021.07.07.451538 doi: bioRxiv preprint 8 MD simulations with coevolutionary analysis and network modeling to present evidence that the SARS-CoV-2 spike protein function as allosterically regulated machine that exploits plasticity of allosteric hotspots to fine-tune response to antibody binding. [77][78][79][80][81][82] These studies showed that examining allosteric behavior of the SARS-CoV-2 pike proteins may be useful to uncover functional mechanisms and rationalize the growing body of diverse experimental data.…”
Section: Computer Simulations and Protein Modelingmentioning
confidence: 99%
“…71 Our recent studies combined coarse-grained and atomistic MD simulations with coevolutionary analysis and network modeling to present evidence that the SARS-CoV-2 spike protein function as allosterically regulated machine that exploits plasticity of allosteric hotspots to fine-tune response to antibody binding. 7782 These studies showed that examining allosteric behavior of the SARS-CoV-2 pike proteins may be useful to uncover functional mechanisms and rationalize the growing body of diverse experimental data. A critical review of computational simulation studies of the SARS-CoV-2 S proteins highlighted the synergies between experiments and simulations, outlining directions for computational biology research in understanding mechanisms of COVID-19 protein targets.…”
Section: Introductionmentioning
confidence: 99%